RESEARCH ON ENERGY EFFICIENCY IN RENOVATION AND RECONSTRUCTION OF BUILDINGS AND STRUCTURES (Conferencea, 2021)
This article describes the system of maintenance of residential buildings, the implementation of repairs and reconstruction (reconstruction).